Citizenship / edited by Richard Bellamy and Antonino Palumbo - "Bellamy, Richard (ed.)" (Surrey, 2010)
Interest in citizenship has never been greater. Politicians of all stripes stress its importance, as do church leaders, captains of industry and every kind of campaigning group. Yet, despite this popularity, the nature and even the very possibility of citizenship has never been more contested. Is citizenship intrinsically linked to political participation or is it essentially a legal status? Does it require membership of a state, or is it only post-national, trans- and possibly supra-national? Is it a universal value that should be the same for all, or does it need to recognise gender and cultural differences? This volume reproduces key articles on these debates - from classic accounts of the historical development of citizenship, to discussions of its contemporary relevance and possible forms in a globalizing world.
Keywords: Citizenship